A blocking scheme for enhancement of distance relay security under stressed system conditions. (January 2018) - Parniani, Mohammad Sahand; Sanaye-Pasand, Majid; Jafarian, Peyman
Highlights: The pattern of change of the voltage magnitude is implicitly included into the decision logic. The separating border between different events is a not a simple fixed value. The changes in the voltage during two subsequent cycles are simultaneously checked to make decision. Fast power swings can be reliably distinguished from fault events. The sequence of passing the defined areas helps to reliably recognize low voltage drop faults. Abstract: Mal-operation of zone-3 of distance relays has been one of the main causes of widespread disturbances and blackouts in power systems throughout the world. Under some non-faulty conditions, the measured impedance may enter zone-3 and cause spurious trip of transmission lines. This can happen during stressed system conditions such as power swing, extreme loading and voltage decline. In this respect, there is an essential need to improve security of zone-3. Introducing a new two-dimensional decision plane, this paper presents a new technique based on superimposed components of voltages magnitude to discriminate non-faulty conditions from fault events. This way, not only the rate of change of the voltage magnitude but also its pattern of change is included into the decision logic. The proposed method is able to provide high security and sensitivity in detecting non-faulty cases and prevents relay from undesired trip in such conditions. The 39-bus New-England test system is used to demonstrate the effectiveness of this method. The obtained results show that the proposed method is able to reliably distinguish stressed conditions from fault events for different power system disturbances and considerably improves security of distance relay.